Spatial reaction engineering approach as an alternative for nonequilibrium multiphase mass‐transfer model for drying of food and biological materials. Issue 1 (17th April 2012) - Putranto, Aditya; Chen, Xiao Dong
Abstract : Drying is a complex process which involves simultaneous heat and mass transfer. Complicated structure and heterogeneity of food and biological materials add to the complexity of drying. Drying models are important for improving dryer design and for evaluating dryer performance. The lumped reaction engineering approach (L‐REA) has been shown to be an accurate and robust alternative for cost‐effective simulations of challenging drying systems. However, more insightful physics has to be shown spatially. In this study, the REA is coupled with the standard mechanistic drying models to yield the spatial‐REA (S‐REA) as nonequilibrium multiphase mass‐transfer model. The S‐REA consists of a system of equations of conservation with the REA representing the local evaporation and wetting rate. Results of the modeling using the S‐REA match well with the experimental data reported previously. This is the first comprehensive REA approach to model the profiles of water vapor concentration during drying of food and biological materials. This study indicates that the S‐REA can be an accurate nonequilibrium multiphase mass‐transfer model with appropriate account of the local evaporation rate. The overall REA concept is expected to contribute substantially for better and cost‐effective representation of transport phenomena of drying process. © 2012 American Institute of Chemical Engineers AIChE J, 59: 55–67, 2013